An Exploratory Study of the Factors Influencing Consumer Behavior in Adopting Free Wi-Fi Services in Yogyakarta: An Approach Based on the Technology Acceptance Model (TAM) - Muhammad Sofiyudin; Budi Sutiono Pratama Nugraha (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyse the factors influencing consumer behavior in adopting free Wi-Fi services in the city of Yogyakarta. The adoption of technology, particularly free Wi-Fi, is a crucial issue in the context of smart cities and enhancing public access to information. This research employs the Technology Acceptance Model (TAM) to explore the impact of perceived usefulness (PU) and perceived ease of use (PEOU) on intention to use, as well as how security concerns and social influence moderate these relationships. The research methodology utilizes Structural Equation Modelling (SEM) with Partial Least Squares (PLS) technique. Data was collected through a survey involving 100 respondents who are users of free Wi-Fi services at various strategic locations in Yogyakarta. The results indicate that perceived usefulness (PU) and perceived ease of use (PEOU) have a significant positive impact on users' intention to adopt free Wi-Fi, while security concerns are found to be a significant inhibitory factor. Additionally, social influence plays a role in enhancing the intention to use free Wi-Fi, although with a smaller effect. This study contributes to the understanding of consumer behavior in adopting free Wi-Fi technology and can serve as a reference for public policy development related to Wi-Fi infrastructure in major cities, particularly in Indonesia.